2013
DOI: 10.1099/ijs.0.042077-0
|View full text |Cite
|
Sign up to set email alerts
|

Endozoicomonas numazuensis sp. nov., a gammaproteobacterium isolated from marine sponges, and emended description of the genus Endozoicomonas Kurahashi and Yokota 2007

Abstract: Two non-motile, rod-shaped gammaproteobacteria were isolated from marine sponges collected from the coast of Japan at Numazu. The isolates were oxidase- and catalase-positive facultative anaerobes that fermented carbohydrates. They required sodium ions for growth and were slightly halophilic, growing in the presence of 1.0–5.0 % (w/v) NaCl (optimum of 2.0 % NaCl). Under aerobic conditions, the major isoprenoid quinones were ubiquinone-9 and menaquinone-9 and the minor quinones were ubiquinone-8 and menaquinone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 15 publications
0
61
0
1
Order By: Relevance
“…Results from this study and other recent reports highlight that members of the Oceanospirillales, specifically, Endozoicomonas spp. are commonly found in marine invertebrates with and without photosymbionts and potentially have important functional roles within their host species (Yang et al, 2010;Nishijima et al, 2012;Speck and Donachie, 2012). Indicator species analysis demonstrated that no OTUs were significantly correlated with invertebrates that do not host photosymbionts, although Rugeria-, Rhodobacteraceae-and Rhodospirillaceae-related sequences were more commonly retrieved in these samples as observed in the redundancy analysis (Figure 1).…”
mentioning
confidence: 67%
“…Results from this study and other recent reports highlight that members of the Oceanospirillales, specifically, Endozoicomonas spp. are commonly found in marine invertebrates with and without photosymbionts and potentially have important functional roles within their host species (Yang et al, 2010;Nishijima et al, 2012;Speck and Donachie, 2012). Indicator species analysis demonstrated that no OTUs were significantly correlated with invertebrates that do not host photosymbionts, although Rugeria-, Rhodobacteraceae-and Rhodospirillaceae-related sequences were more commonly retrieved in these samples as observed in the redundancy analysis (Figure 1).…”
mentioning
confidence: 67%
“…S3 in the Supplement). Endozoicomonas have been found in sponges (some under the name Spongiobacter) (Thiel et al 2007, Mohamed et al 2008, Nishijima et al 2013, bivalves (Zielinski et al 2009, Jensen et al 2010, ascidians (Martínez-García et al 2007), a nudibranch (Kurahashi & Yokota 2007), polychaetes (Goffredi et al 2007), sea anemones (Schuett et al 2007, Du et al 2010, starfish (Choi et al 2010), scleractinian corals (Bourne & Munn 2005, Bourne et al 2008, Hansson et al 2009, Littman et al 2009, Raina et al 2009, Sunagawa et al 2010, Speck & Donachie 2012, and different tropical gorgonians and other soft corals (Webster & Bourne 2007, Sunagawa et al 2010). In the Caribbean gorgonian Gorgonia ventalina, the most common bacteria are Endozoicomonas.…”
Section: Discussionmentioning
confidence: 99%
“…( Gammaproteobacteria ; Oceanospirillales ) are dominant members of the bacterial community associated with diverse marine invertebrates, including corals (16), sponges (7), gorgonians (8, 9), molluscs (1013), and tubeworms (14), as well as a basal chordate (15). In some hosts, these bacteria have been observed intracellularly (2, 11, 13).…”
Section: Genome Announcementmentioning
confidence: 99%